Usefulness of Early Extracorporeal Shock Wave Lithotripsy in Colic Patients with Ureteral Stones - Choi, Hyeung Joon (The Korean Urological Association, 2012)
PURPOSE: To compare efficacy and safety between early extracorporeal shock wave lithotripsy (eESWL) and deferred ESWL (dESWL) in colic patients with ureteral stones and to investigate whether eESWL can play a critical role in improving treatment outcomes. MATERIALS AND METHODS: A total of 279 patients who underwent ESWL for single radio-opaque ureteral stones of 5 to 20 mm in size were included in this retrospective study. The patients were categorized into two groups according to the time between the onset of colic and ESWL: eESWL (<48 hours, n=153) and dESWL (≥48 hours, n=126). Success was defined as stone-free status as shown on a plain radiograph within 1 month of the first session. RESULTS: For all patients, the success rate in the eESWL group was significantly higher than that in the dESWL group. The eESWL group required significantly fewer ESWL sessions and less time to achieve stone-free status than did the dESWL group. For 241 patients with stones <10 mm, all treatment outcomes in the former group were superior to those in the latter group, but not for 38 patients with stones sized 10 to 20 mm. The superiority of eESWL over dESWL in the treatment outcomes was more pronounced for proximal ureteral stones than for mid-to-distal ureteral stones. Post-ESWL complication rates were comparable between the two groups. In the multivariate analysis, smaller stone size and a time to ESWL of <48 hours were independent predictors of success. CONCLUSIONS: Our data suggest that eESWL in colic patients with ureteral stones is an effective and safe treatment with accelerated stone clearance.